Nursing Professional Pride Scale: Turkish adaptation and psychometric properties. Issue 1 (24th April 2021) - Aydin, Adeviye; Erbas, Atiye; Kaya, Yunus
Abstract: Purpose: This study established the Turkish validity and reliability of the Nursing Professional Pride Scale (NPPS). Design and Methods: The study was a descriptive and cross‐sectional conducted in Turkey. The sample consisted of 301 nurses with at least one year of work experience. Data were collected online between August and September 2020 and analyzed using the SPSS 25.0 and LISREL 8.80. Confirmatory factor analysis, linguistic and content validity, and reliability analyses were performed. Findings: The Turkish version of the Nursing Professional Pride Scale (NPPS‐TR) had a content validity index of 0.95 and Cronbach's alpha of 0.89 and a five‐factor structure with acceptable psychometric properties ( χ 2 /df = 2.85, RMSEA = 0.079, CFI = 0.92, SRMR = 0.08). Practice implications: The NPPS‐TR is a valid and reliable measure of professional pride in Turkish nurses.